Design and simulation of Dual Z-Source Dual-Input Hybrid 2/3 level inverter. (3rd September 2022) - Akbari, Rasoul; Hosseinpour, Majid; Ahmadi, Mahsa
ABSTRACT: The 2/3-level hybrid inverters are a combination of three-level Neutral Point Clamped (NPC) inverter and conventional two-level inverter, which has the advantage of both two-level and three-level structures with fewer switches than the NPC inverter. In this paper, a new structure of 2/3 hybrid inverter based on dual-Z-‏source network is proposed. The proposed structure improves the performance of the 2/3-level inverter and increases its independent DC input voltages. The output voltage gain can be obtained by selecting the shoot-through interval appropriately in dual Z-source networks. In addition, shoot-through intervals in Z-source networks allow the inverter to run without dead time, thus increasing the output voltage quality. A modified switching method is presented for the proposed inverter, and the necessary calculations are performed. The proposed structure can be used to connect different distributed generation sources to the load separately from the grid or to the low-pressure network. The performed simulations show the accuracy of the proposed structure.